About the endothermal transitions of galactomannans: A multi-analytical DSC, LF-1H NMR and DMA study. (1st May 2019) - Busch, Verónica M.; Santagapita, Patricio R.; Díaz-Calderón, Paulo; Enrione, Javier I.; Buera, M. Pilar
Graphical abstract: Highlights: 3 endothermal transitions of galactomannans were observed in DSC thermograms. Low ΔCp, wide ΔT and no typical wc dependence complicated Tg assignment. An enthalpic relaxation-type transition around 50 °C was wc & frequency independent. NMR T2 temperature dependence changed close to the low temperature transition. Sinusoidal shape of FID NMR signals disappeared by increasing temperature or wc. Abstract: The thermal transitions of biopolymers were subject of great discussion in the 90s due to their relevance in structure development during processing and stability on storage. In the present work two galactomannans, vinal gum and guar gum, were evaluated by DSC, DMA and LF- 1 H NMR in order to compare them, establishing their potential operational application range and promoting the use of the non-conventional VG in foods or other products. Three endothermal transitions appeared when heating the samples in the DSC: one at temperatures −90 to −10 °C (LTT), other around 50 °C (MTT) and a third one between 50 and 100 °C (HTT). Both LTT and HTT showed water content dependence and low Δ Cp values, which difficulted the assignment of a glass transition. MTT appeared as an enthalpic relaxation independent on frequency or on water content. This transition was related to changes in mechanical properties and with the stabilization of proton mobility.